2001
DOI: 10.1097/00001648-200103000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Exacerbation of Asthma in African-American Children in Los Angeles

Abstract: Significant increases in asthma morbidity and mortality in the United States have occurred since the 1970s, particularly among African-Americans. Exposure to various environmental factors, including air pollutants and allergens, has been suggested as a partial explanation of these trends. To examine relations between several air pollutants and asthma exacerbation in African-Americans, we recruited a panel of 138 children in central Los Angeles. We recorded daily data on respiratory symptoms and medication use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
155
3
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(170 citation statements)
references
References 26 publications
7
155
3
5
Order By: Relevance
“…O 3 and temperature have a synergistic effect on several outcomes: asthma attacks, morning PEF and eye irritation. Together with climate and pollutants, ambient aeroallergens also influence asthma [20,28]. In the present study, only pollen count was available, and O 3 and pollen count had a synergistic effect on the risk of asthma attacks.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…O 3 and temperature have a synergistic effect on several outcomes: asthma attacks, morning PEF and eye irritation. Together with climate and pollutants, ambient aeroallergens also influence asthma [20,28]. In the present study, only pollen count was available, and O 3 and pollen count had a synergistic effect on the risk of asthma attacks.…”
Section: Discussionmentioning
confidence: 68%
“…In the first [19], in which 83 African-American asthmatic children were studied during a 4-month summer period, particles with a 50% cut-off aerodynamic diameter of 10 mm (PM10) and O 3 were associated with shortness of breath, but not coughing and wheezing. In the second study [20], which included 138 children, the occurrence of shortness of breath, cough and wheeze was associated with PM10, particles with a 50% cut-off aerodynamic diameter of 2.5 mm (PM2.5), NO 2 and moulds, but not with O 3 and pollen, and the use of extra asthma medication was associated to PM10 and O 3 . During summer asthma camps in Connecticut, USA, O 3 and fine particles (sulphate and hydrogen ions) were found to be significantly correlated with asthma exacerbation, chest symptoms, medication use and decreases in lung function [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of panel studies have demonstrated a relationship between levels of airborne particulate matter less than 10 or 2.5 mm in aerodynamic diameter (PM 10 or PM 2.5 ) and acute asthma severity indices including hospital admissions (1)(2)(3), declines in pulmonary function, and increases in medication use and symptoms (4)(5)(6)(7)(8)(9)(10)(11)(12). Almost all such studies estimate ambient health effects without taking into account concurrent exposures that may impact asthma, such as environmental tobacco smoke (ETS).…”
mentioning
confidence: 99%
“…*Published emission factors but not reported in text. **Emission factors reported explicitly in text ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Environmental Benefits Mapping and Analysis Program using the concentration response function from chronic bronchitis [63], acute bronchitis [64], all-cause mortality [65,104], COPD hospitalization (Moolgavgkar 2000a, 2003) [66], asthma emergency room visits [67], work loss days [68], asthma (symptoms) [69], minor-restricted activity days [70], acute MI [71], respiratory disease [72], lower respiratory symptoms [73], and cough among asthmatic children [74]; D Probable, but not specified explicitly in the text; ᴱ Health And Air Pollution Study in New Zealand to estimate the morbidity and mortality health costs associated with traffic emissions [82]; F CVD admission >64 years: [75]; ᴳ Mortality: <75 and >75 years, respiratory disease (65 years) [76], and lung cancer [104] Morbidity: CVD, respiratory disease [76], and lung cancer [104]; H Method of transport emission estimation is quite vague in determination of emission factors; I External cost of energy to estimate the automotive pollution impact on health in Europe [81]; J Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; K Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach. …”
Section: Resultsmentioning
confidence: 99%